Impact of a sustained Cooperative Learning intervention on student motivation. (2nd January 2017) - Fernandez-Rio, Javier; Sanz, Naira; Fernandez-Cando, Judith; Santos, Luis
Abstract : Background : Cooperative Learning has been recently defined as a true pedagogical model. Moreover, in a recent review Casey and Goodyear reported that it can help physical education promote the four basic learning outcomes: physical, cognitive, social and affective. Purpose : The main goal was to investigate the impact of a sustained Cooperative Learning intervention on student motivation. The second goal was to assess students' perceptions of the Cooperative Learning class climate. Finally, the third goal was to explore students' feelings and thoughts after experiencing Cooperative Learning in physical education for an extended period of time. Participants and settings: 249 students (grades 8–11) and 4 teachers enrolled in 4 different high schools agreed to participate. Each school administration allocated several class groups to each teacher based on its necessities. Therefore, intact physical education classes played a part in this research project. They were randomly distributed into an experimental group with 137 students (mean age 13.91 ± 1.76 years), which experienced 3 consecutive cooperative learning units, and a comparison group with 112 students (mean age 13.41 ± 1.25 years), which experienced a traditional teaching approach during the same length of time. Research design : A pre-test, post-test, quasi-experimental, comparison group design was followed. Data collection: Prior to and at the end of the intervention programme, all participating students were asked to complete a questionnaire, which included the Perceived Locus of Causality Scale and the subscale 'Cooperative Learning' of the Perceived Motivational Climate Questionnaire. At post-test, participants in the experimental group were also asked to: 'Describe your feelings, your thoughts and your ideas on the three Cooperative Learning units that you just experienced in physical education'. Data analysis: Quantitative data was analysed using SPSS 22.0, while MAXQDA 11 was used to assist with qualitative data management. Findings: Quantitative data showed an increase in intrinsic motivation and identified regulation only in the experimental group. This group also increased its perceptions of a Cooperative Learning class climate. Qualitative data analysis of the students' responses after experiencing Cooperative Learning on a sustained basis produced five major themes: cooperation, relatedness, enjoyment, novelty and disappointment. All these findings are in line with Vallerand's hierarchical model of motivation, where social factors (i.e. Cooperative Learning) influence psychological mediators (i.e. relatedness), which mediate over the different types of motivation (i.e. intrinsic motivation) and finally lead to different outcomes (i.e. enjoyment). Conclusion : Cooperative Learning applied on a sustained basis can increase the most self-determined types of motivation, intrinsic motivation and identified regulation, in secondary education students. Students' perceptions after experiencing Cooperative Learning for a long period of time reflected four positive ideas: cooperation, relatedness, enjoyment and novelty and a negative one: disappointment. Both the positive and the negative ideas should be considered when implementing Cooperative Learning in physical education, because students experience them.